2020
DOI: 10.1177/1359105320967422
|View full text |Cite
|
Sign up to set email alerts
|

Mumbod? A comparison of body image and dietary restraint among women with younger, older, and no children

Abstract: Pregnancy and the postpartum period are times of significant body, and body image changes for women. Adult women ( N = 885) aged 21 to 47 years old completed an online questionnaire. Mothers of young children (0–5 years) had significantly lower levels of body shame, self-objectification, and dietary restraint than women without children, and women with school-aged (6–10 years) children had significantly lower self objectification than women without children, once we controlled for age. BMI predicted body shame… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 53 publications
0
8
0
Order By: Relevance
“…One explored the pathways between body surveillance and disordered eating in mothers and found that this pathway was exacerbated by body shame and attenuated by body functionality appreciation, but only in mothers who were breastfeeding (Donati Beech et al, 2020). The other explored differences in self-objectification, body shame, internalization of appearance ideals, and body appreciation in women and found that those with children had higher levels of body shame than those who did not (Yager et al, 2020). Moreover, these authors found that, for the mothers in their sample, there was a positive relationship between body shame and body mass index (BMI).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…One explored the pathways between body surveillance and disordered eating in mothers and found that this pathway was exacerbated by body shame and attenuated by body functionality appreciation, but only in mothers who were breastfeeding (Donati Beech et al, 2020). The other explored differences in self-objectification, body shame, internalization of appearance ideals, and body appreciation in women and found that those with children had higher levels of body shame than those who did not (Yager et al, 2020). Moreover, these authors found that, for the mothers in their sample, there was a positive relationship between body shame and body mass index (BMI).…”
Section: Resultsmentioning
confidence: 99%
“…In addition, breastfeeding mothers reported higher body functionality appreciation and less body surveillance, body shame, and disordered eating compared to non-breastfeeding mothers. Yager et al (2020) explored differences in self-objectification, body shame, internalization of appearance ideals, and body appreciation in samples of women within two distinct postpartum brackets (youngest child < 5 years old; youngest child 6–10 years old) and a control group of women with no children. After controlling for age, BMI, and level of education, no significant differences were found among the three groups of women on any variable.…”
Section: Resultsmentioning
confidence: 99%
“…Family eating habits have the greatest influence over young children's diets [49], and one study showed that dietary indicators of mothers was a strong predictor of children's dietary quality [50]. Although there is a large volume of research demonstrating the relationship between mothers' and children's food restraint and eating behaviours [51,52], no studies were found comparing dietary recommendations or quality between women with or without children. Our results reinforce the need for increased education to women and families to encourage healthy eating habits, as they are clear role models to their children.…”
Section: Discussionmentioning
confidence: 99%
“…Early motherhood is typically an exciting time, but this period is also associated with significant physical, psychological, and social change (Gross and Marcussen, 2017). Alterations to women’s body image after pregnancy, childbirth, and early child-rearing is a common but poorly understood phenomenon (Grogan, 2017; Yager et al, 2020). The complexities of body image in early motherhood are important to understand given changes may significantly impact the wellbeing of both mothers and their infants due to the associated relationships with physical and mental health outcomes (Fern et al, 2014; Silveira et al, 2015).…”
mentioning
confidence: 99%
“…Despite the negative body image that some women experience postpartum, positive body image experiences have also been reported in early motherhood. This includes a new appreciation of body functionality after the amazing feats of pregnancy and postpartum infant care (Fern et al, 2014; Fox and Neiterman, 2015; Yager et al, 2020). Some women report feeling stronger and fitter postpartum and are more positive about their bodies in the initial weeks after birth (Clark et al, 2009a; Strang and Sullivan, 1985).…”
mentioning
confidence: 99%